Prevalence and factors associated with occupational health problems among leather footwear manufacturing workers in Ambur town, Thirupathur district, Tamil Nadu, India - D., Judyangel; R., Thilagavathi; M., Prakash (International Journal Of Community Medicine And Public Health, 2022)
Background: In India, the leather footwear manufacturing sector contributes to a significant segment of leather products, and workers were exposed to a wide range of hazardous substances during the manufacturing process. The present study was conducted to identify the prevalence of various work-related health complaints and the factors associated with occupational health problems among leather footwear workers in Tamil Nadu. Methods: This cross-sectional study was conducted among 275 leather footwear workers in Ambur town, Thirupathur district, Tamil Nadu from June 2019 to July 2019. Data was collected using a semi-structured questionnaire consisting of socio-demographic and workplace characteristics, work-related self-reported health complaints, and use of personal protective equipment (PPE). Descriptive analysis and multivariate analysis were performed to identify factors associated with work-related health problems at a 5% level of significance. Results: The study demonstrated a prevalence of 19.33% respiratory disorders, 16.4% skin ailments, and 37% musculoskeletal complaints. Workers involved in the scouring/finishing process had nearly two times the odds (95% CI: 0.977-3.923); workers who do not use PPE like gloves or masks had two times the odds (95% CI: 1.307-4.346); workers who reported inadequate windows/fans or blowers in their work station had four times the odds (95% CI: 1.421-12.413) and workers who reported lack of regular work training had 3.5 times odds (95% CI: 1.954-6.531) of occupational health problems. Conclusions: Implementation of strict protocols on the use of PPE, periodic monitoring and safety training should be regulated to prevent the workers from these health problems.